3D CT Angiography - Kalender, Willi Alfred; Prokop, Mathias (Taylor and Francis, 2023)
Spiral CT angiography (CTA) is a relatively new volumetric or truly three-dimensional approach to vascular imaging, but it also makes use of older and known techniques. This chapter presents the basic and common features of all CTA techniques, includes information on practical aspects such as contrast medium application, discusses image quality aspects in detail, and gives an overview of clinical applications. Spiral CT allows continuous volume data acquisition instead of the traditional way of scanning slice by slice successively. It was presented for the first time in 1989 and has gained a dominant role since then. When spiral CT was introduced, there was a lot of concern that image quality might be impaired due to moving the patient and the resulting non-planar scan geometry. A CTA examination is, in most cases, preceded by a standard CT examination without contrast medium application.
CRIS-Team Scopus Importer:2023-09-15

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

A low-radiation exposure protocol for 3D QCT of the spine - Museyko, Oleg; Heinemann, A.; Krause, M.; Wulff, B.; Amling, M.; Pueschel, K.; Glueer, C. C.; Kalender, Willi Alfred; Engelke, Klaus (Osteoporosis international, 2014)
Cadaver and phantom measurements and simulations confirmed that radiation exposure in 3D QCT of the spine can be reduced if 80 kV instead of 120 kV protocols are used; 120 mAs and slice thicknesses of 1-1.3 mm should be usable but obese patient will require higher milliampere-second settings.To develop a low-radiation exposure CT acquisition protocol for 3D QCT of the thoracolumbar spine.Twenty-six cadavers were scanned with a standard protocol of 120 kV, 100 mAs and with a low-dose protocol using 90 kV, 150 mAs. The scan range included the vertebrae T6 to L4. Each vertebra was segmented and the integral volume and BMD of the total vertebral body were determined. Effective dose values were estimated. The impact of milliampere-second reduction on image quality was simulated by adding noise.One hundred ninety-six vertebrae were analyzed. Integral volume as well as integral BMD correlated significantly (p < 0.001) between standard and low-dose protocols (volume, r (2) = 0.991, residual root mean square (RMS) error, 0.77 cm(3); BMD, r (2) = 0.985, RMS error, 4.21 mg/cm(3)). The slope significantly differed from 1 for integral BMD but not for volume hinting at residual field inhomogeneity differences between the two voltage settings that could be corrected by cross-calibration. Compared to the standard protocol, effective dose was reduced by over 50 % in the low-dose protocol. Adding noise in the 90 kV images to simulate a reduction from 150 to 100 mAs did not affect the results for integral volume or BMD.For 3D QCT of the spine, depending on scanner type, 80 or 90 kV instead of 120 kV protocols may be considered as an important option to reduce radiation exposure; 120 mAs and slice thicknesses of 1-1.5 mm are usable if segmentation is robust to noise. In obese patients, higher milliampere-second settings will be required.
EVALuna2:10069

Brust-CT als alternative Bildgebung im Brustkrebs-Screening in Deutschland: das ProHTA-Simulationskonzept - Meier, Florian; Ruile, Georg; Djanatliev, Anatoli; Kriza, Christine; Leb, Ines; Schöffski, Oliver; Kalender, Willi Alfred; Kolominsky-Rabas, Peter (Tagungsband der 7. Jahrestagung der Deutschen Gesellschaft für Gesundheitsökonomie, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.brustc

Comparative investigation of the detective quantum efficiency of direct and indirect conversion detector technologies in dedicated breast CT - Kuttig, Jan; Steiding, Christian; Kolditz, Daniel; Hupfer, Martin; Karolczak, Marek; Kalender, Willi Alfred (Physica Medica, 2015)
To investigate the dose saving potential of direct-converting CdTe photon-counting detector technology for dedicated breast CT.We analyzed the modulation transfer function (MTF), the noise power spectrum (NPS) and the detective quantum efficiency (DQE) of two detector technologies, suitable for breast CT (BCT): a flat-panel energy-integrating detector with a 70 ?m and a 208 ?m thick gadolinium oxysulfide (GOS) and a 150 ?m thick cesium iodide (CsI) scintillator and a photon-counting detector with a 1000 ?m thick CdTe sensor.The measurements for GOS scintillator thicknesses of 70 ?m and 208 ?m delivered 10% pre-sampled MTF values of 6.6 mm(-1) and 3.2 mm(-1), and DQE(0) values of 23% and 61%. The 10% pre-sampled MTF value for the 150 ?m thick CsI scintillator 6.9 mm(-1), and the DQE(0) value was 49%. The CdTe sensor reached a 10% pre-sampled MTF value of 8.5 mm(-1) and a DQE(0) value of 85%.The photon-counting CdTe detector technology allows for significant dose reduction compared to the energy-integrating scintillation detector technology used in BCT today. Our comparative evaluation indicates that a high potential dose saving may be possible for BCT by using CdTe detectors, without loss of spatial resolution.
EVALuna2:10106

Dedicated Breast Computed Tomography with a Photon-Counting Detector: Initial Results of Clinical in Vivo Imaging - Berger, Nicole; Marcon, Magda; Saltybaeva, Natalia; Kalender, Willi Alfred; Alkadhi, Hatem; Frauenfelder, Thomas; Boss, Andreas (Investigative Radiology, 2019)
The purpose of this work is to present the data obtained from the first clinical in vivo application of a new dedicated spiral breast computed tomography (B-CT) equipped with a photon-counting detector. Materials and Methods The institutional review board approved this retrospective study. Twelve women referred for breast cancer screening were included and underwent bilateral spiral B-CT acquired in prone position. Additional sonography was performed in case of dense breast tissue or any B-CT findings. In 3 women, previous mammography was available for comparison. Soft tissue (ST) and high-resolution (HR) images were reconstructed. Two independent radiologists performed separately the readout for subjective image quality and for imaging findings detection. Objective image quality evaluation was performed in consensus and included spatial resolution, contrast resolution, signal-to-noise ratio (SNR), and contrast-to-noise ratio. All women were asked to report about positioning comfort and overall comfort during data acquisition. Results The major pectoral muscle was included in 15 breast CT scans (62.5%); glandular component was partially missing in 2 (8.3%) of the 24 scanned breasts. A thin "ring artifact" was present in all scans but had no influence on image interpretations; no other artifacts were present. Subjective image quality assessment showed excellent agreement between the 2 readers (κ = 1). Three masses were depicted in B-CT and were confirmed as simple cysts in sonography. Additional 5 simple cysts and 2 solid benign lesions were identified only in sonography. A total of 12 calcifications were depicted with a median size of 1.1 mm (interquartile range, 0.7-1.7 mm) on HR and 1.4 mm (interquartile range, 1.1-1.8 mm) on ST images. Median SNRgl, SNRfat, and contrast-to-noise ratio were significantly higher in ST than in HR reconstructions (each, P < 0.001). A mild discomfort due to positioning of the rib cage on the table was reported by 2 women (16.7%); otherwise, no discomfort was reported. Conclusions The new dedicated B-CT equipped with a photon-counting detector provides high-quality images with potential for screening of breast cancer along with minor patient discomfort.
CRIS-Team Scopus Importer:2019-06-28
Keywords: breast cancer screening; breast CT; mammography

Dose Optimization for Computed Tomography Localizer Radiographs for Low-Dose Lung Computed Tomography Examinations - Schmidt, Bernhard Magnus Wilhelm; Hupfer, Martin; Saltybaeva, Natalia; Kolditz, Daniel; Kalender, Willi Alfred (Investigative Radiology, 2017)
INTRODUCTION: Recent studies have shown a substantial reduction of radiation dose from computed tomography (CT) scans down to 0.1 mSv for lung cancer screening and cardiac examinations, when applying optimization techniques. Hence, CT localizer radiographs (LRs) might now be considered a significant contributor to the total dose of the CT examination. We investigated in our study the potential for reducing dose of the LRs by adapting the patient-specific acquisition parameters of the LR. MATERIALS AND METHODS: Localizer radiographs covering the lungs were acquired on 2 clinical scanners (64 slices, conventional detector [CD]; 96 slices, fully integrated detector [ID]) for 3 semianthropomorphic phantoms, representing a slim, a normal, and an obese adult. Starting at 120-kV tube voltage and 250-mA current were reduced until the image quality of the LR, and thereby the accuracy of the automatic exposure control was compromised; this was defined as a deviation of measured attenuation values in the center of the LR of more than 5% from the reference values measured at the highest tube voltage and current. Subsequent Monte Carlo calculations on anthropomorphic phantoms were performed to calculate organ and effective dose values for the respective optimal settings. In addition, effective dose values normalized to CTDIvol for tube voltages ranging from 60 to 160 kV were determined for the different combinations of phantom sizes, sexes, and LR views to evaluate dose efficiency. RESULTS: For the CD scanner, the optimal LR settings depended strongly on phantom size. Higher tube voltage and current were necessary for the larger phantoms. The ID scanner showed uncompromised LR quality for all phantoms using the lowest possible tube voltage-tube current combination of 80 kV and 20 mA. Depending on patient size and LR direction, effective dose values for the optimal settings ranged from 6 to 53 μSv and 3 to 11 μSv for the CD and ID scanner, respectively. For the example of an anterior-posterior LR on a normal patient, using the optimal settings instead of the standard settings on the ID scanner reduced LR dose from 53 μSv (120 kV, 30 mA) to 10 μSv (80 kV, 20 mA). The simulations for the different tube voltages show that effective dose and CTDIvol behave similarly for different views and patient sizes. However, the tube voltage level itself impacts the relationship between CTDIvol and effective dose, by up to a factor of 2. DISCUSSION: Dose from LRs may contribute significantly to the total effective dose of low-dose CT examinations such as lung cancer screening. Optimal LR settings can reduce LR dose substantially, but adaptations have to consider scanner characteristics, detector technology, and patient size. Thus, for low-dose CT examinations, such as cardiac examinations and lung cancer screening, LR optimization may result in a significant dose reduction and thereby in a substantial reduction of total dose.
EVALuna2:33261

Dynamic contrast-enhanced micro-computed tomography correlates with 3-dimensional fluorescence ultramicroscopy in antiangiogenic therapy of breast cancer xenografts - Poeschinger, Thomas; Renner, Anja; Eisa, Fabian; Dobosz, Michael; Strobel, Steffen; Weber, Thomas G.; Brauweiler, Robert; Kalender, Willi Alfred; Scheuer, Werner (Investigative Radiology, 2014)
Dynamic contrast-enhanced (DCE) micro-computed tomography (micro-CT) has emerged as a valuable imaging tool to noninvasively obtain quantitative physiological biomarkers of drug effect in preclinical studies of antiangiogenic compounds. In this study, we explored the ability of DCE micro-CT to assess the antiangiogenic treatment response in breast cancer xenografts and correlated the results to the structural vessel response obtained from 3-dimensional (3D) fluorescence ultramicroscopy (UM).Two groups of tumor-bearing mice (KPL-4) underwent DCE micro-CT imaging using a fast preclinical dual-source micro-CT system (TomoScope Synergy Twin, CT Imaging GmbH, Erlangen, Germany). Mice were treated with either a monoclonal antibody against the vascular endothelial growth factor or an unspecific control antibody. Changes in vascular physiology were assessed measuring the mean value of the relative blood volume (rBV) and the permeability-surface area product (PS) in different tumor regions of interest (tumor center, tumor periphery, and total tumor tissue). Parametric maps of rBV were calculated of the tumor volume to assess the intratumoral vascular heterogeneity. Isotropic 3D UM vessel scans were performed from excised tumor tissue, and automated 3D segmentation algorithms were used to determine the microvessel density (MVD), relative vessel volume, and vessel diameters. In addition, the accumulation of coinjected fluorescence-labeled trastuzumab was quantified in the UM tissue scans to obtain an indirect measure of vessel permeability. Results of the DCE micro-CT were compared with corresponding results obtained by ex vivo UM. For validation, DCE micro-CT and UM parameters were compared with conventional histology and tumor volume.Examination of the parametric rBV maps revealed significantly different patterns of intratumoral blood supply between treated and control tumors. Whereas control tumors showed a characteristic vascular rim pattern with considerably elevated rBV values in the tumor periphery, treated tumors showed a widely homogeneous blood supply. Compared with UM, the physiological rBV maps showed excellent agreement with the spatial morphology of the intratumoral vascular architecture. Regional assessment of mean physiological values exhibited a significant decrease in rBV (P < 0.01) and PS (P < 0.05) in the tumor periphery after anti-vascular endothelial growth factor treatment. Structural validation with UM showed a significant reduction in reduction of relative vessel volume (rVV) (P < 0.01) and MVD (P < 0.01) in the corresponding tumor region. The reduction in rBV correlated well with the rVV (R = 0.73 for single values and R = 0.95 for mean values). Spatial maps of antibody penetration showed a significantly reduced antibody accumulation (P < 0.01) in the tumor tissue after treatment and agreed well with the physiological change of PS. Examination of vessel diameters revealed a size-dependent antiangiogenic treatment effect, which showed a significant reduction in MVD (P < 0.001) for vessels with diameters smaller than 25 ?m. No treatment effect was observed by tumor volume.Noninvasive DCE micro-CT provides valuable physiological information of antiangiogenic drug effect in the intact animal and correlates with ex vivo structural analysis of 3D UM. The combined use of DCE micro-CT with UM constitutes a complementary imaging toolset that can help to enhance our understanding of antiangiogenic drug mechanisms of action in preclinical drug research.
EVALuna2:10086

Effekte eines Ganzkörpervibrationstrainings auf Parameter des Frakturrisikos - von Stengel, Simon; Kemmler, Wolfgang; Mayer, Sabine; Engelke, Klaus; Klarner, Andreas; Kalender, Willi Alfred (Deutsche Medizinische Wochenschrift, 2009)

Effekte sportlichen Trainings auf gesundheitliche Risikofaktoren und Gesundheitskosten über 65jährigen Frauen - Kemmler, Wolfgang; von Stengel, Simon; Engelke, Klaus; Mayer, Sabine; Kalender, Willi Alfred (Deutsche Zeitschrift für Sportmedizin, 2009)

Effekte von Ganzkörpervibrationen auf die neuromuskuläre Leistungsfähigkeit von Frauen über dem 65. Lebensjahr. Einjahresergebnisse der kontrollierten randomisierten ELVIS-Studie - Kemmler, Wolfgang; von Stengel, Simon; Mayer, Sabine; Hoffmann, Martina; Hentschke, Christian; Kalender, Willi Alfred (Zeitschrift für Gerontologie und Geriatrie, 2010)
Sarkopenie ist mit einem erhöhten Risiko für Morbidität und Mortalität des älteren Menschen verbunden. Ganzkörpervibrationstraining (Whole-Body-Vibration, WBV) wird derzeit als „sanfte“ Alternative zu konventionellem Muskeltraining diskutiert. Die vorliegende Studie sollte klären, ob WBV die trainingsinduzierte Wirkung auf die Muskelmasse, die neuromuskuläre Leistungsfähigkeit und die Sturzhäufigkeit verbessern kann. Insgesamt 151 postmenopausale Frauen wurden randomisiert auf drei Gruppen verteilt: Trainingsgruppe (TG), Trainingsgruppe mit Vibration (VTG) und Kontrollgruppe (KG). Die TG absolvierte über 12 Monate zweimal pro Woche ein Multifunktionstraining u. a. mit einem Beinkraftzirkel ohne WBV, während die VTG dasselbe Programm mit einem Beinkrafttraining unter WBV durchführte. Die Messungen erfolgten zu Beginn und nach 12 Monaten. Trotz positiver Veränderung der fettfreien Körpermasse innerhalb beider Sportgruppen zeigte sich kein signifikanter Zwischengruppenunterschied. Beide TG verbesserten ihre Rumpfkraft jeweils signifikant (vs. KG). Auch die Beinkraft verbesserte sich in beiden TG, aber lediglich die VTG wies signifikante Unterschiede zur KG auf. Ebenfalls nur die VTG zeigte ein im Vergleich zur KG signifikant niedrigeres Risiko für Stürz

Einfluss körperlichen Trainings auf Risikofaktoren der Fraktur bei älteren Frauen - vorläufige Ergebnisse der Senioren Fitness und Präventionsstudie (SEFIP) - Kemmler, Wolfgang; von Stengel, Simon; Mayer, Sabine; Engelke, Klaus; Kalender, Willi Alfred (Osteologie, 2007)
UnivIS-Import:2015-04-14:Pub.2007.phil.dps.iss.psbg.einflu_7

Erste Ergebnisse der Erlanger Longitudinalen Vibrationsstudie (ELVIS) - von Stengel, Simon; Kemmler, Wolfgang; Mayer, Sabine; Engelke, Klaus; Kalender, Willi Alfred (Osteologie, 2007)
UnivIS-Import:2015-03-09:Pub.2007.phil.dps.iss.psbg.erstee

Exercise, Body Composition, and Functional Ability. A Randomized Controlled Trial - Kemmler, Wolfgang; von Stengel, Simon; Engelke, Klaus; Häberle, Lothar; Mayhew, Jerry; Kalender, Willi Alfred (American Journal of Preventive Medicine, 2010)
Context In women, age and the menopausal transition contribute to an increase of body fat and a reduction of lean body mass associated with functional decline, affecting independent living. Background Sarcopenia and adiposity in the elderly has been associated with increased mortality and functional decline affecting independent living. Purpose This study was conducted to determine the effect of a multipurpose exercise program on the body composition and functional ability of elderly women living in a community. Design An 18-month single-blinded RCT comparing participants in an exercise program with an active control group was conducted from May 2005 through December 2007. Analyses were conducted from January 2008 to July 2008. Setting/participants Two hundred forty-six women (aged 69.1±4.0 years) living independently in the area of Erlangen–Nürnberg (Germany) participated in the study. Intervention Subjects (n=123) performed a multipurpose exercise program with special emphasis on exercise intensity but with low-level requirements for training facilities and materials. The 123 women in the control group focused primarily on well-being. Main outcome measures Body composition was assessed by dual-energy x-ray absorptiometry. Further, strength was evaluated using isometric techniques for the back and legs. Aerobic fitness was determined from a progressive-intensity treadmill test. Results After 18 months, significant effects in favor of the exercise program for body composition were increases in appendicular skeletal muscle mass and lean body mass along with reductions in abdominal fat and total body fat. Significant performance effects also favored the exercise program and included enhanced isometric maximum trunk-extensor and leg press strength, leg press power, timed up-and-go test, and aerobic fitness. Conclusions A high-intensity multipurpose exercise program produced significant improvements in body composition and functional ability in a cohort of elderly women living in a community.

Exercise effects on fall risk and bone integrity. Preliminary results of the Senior Fitness and Prevention Study (SEFIP) - Kemmler, Wolfgang; von Stengel, Simon; Bebenek, Michael; Mayer, Sabine; Engelke, Klaus; Kalender, Willi Alfred; Mayhew, Jerry (Medicine and science in sports and exercise, 2008)
UnivIS-Import:2015-04-14:Pub.2008.phil.dps.iss.psbg.exerci

Flat panel detector angiographic CT for stent-assisted coil embolization of broad-based cerebral aneurysms - Richter, Gregor; Engelhorn, Tobias; Struffert, Tobias; Dölken, Marc; Ganslandt, Oliver; Hornegger, Joachim; Kalender, Willi Alfred; Dörfler, Arnd (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The purpose of this work was to evaluate angiographic CT (ACT) in the combined application of a self-expanding neurovascular stent and detachable platinum coils in the management of broad-based and fusiform intracranial aneurysms. MATERIALS AND METHODS: Eleven patients harboring wide-necked intracranial aneurysms were treated with a flexible self-expanding neurovascular stent and subsequent aneurysm embolization with platinum microcoils. ACT was performed after the interventional procedure to analyze stent position and the relationship of coils to the stent. Postprocessing included multiplanar reconstructions (MPRs) and maximum intensity projections (MIPs). ACT volume datasets were postprocessed for soft tissue visualization. RESULTS: Accurate stent placement with subsequent coil occlusion of the aneurysms was feasible in all of the patients. Similar to nonsubtracted digital subtraction angiography (DSA) images, radiopaque platinum stent markers showed excellent visibility in ACT as well. The stent struts themselves, hardly visible in nonsubtracted DSA, were visible in MPRs and MIPs of ACT in all of the patients. In aneurysms larger than 10 mm in diameter, accurate stent assessment at the level of the coils was limited due to beam hardening artifacts. Postprocedural ACT in all of the patients did not reveal any evidence of procedure-related intracranial hemorrhage. CONCLUSION: ACT provides cross-sectional, 3D visualization of endovascular stents otherwise hardly visible with plain fluoroscopy. ACT enables us to accurately determine stent position, which may be helpful in complex stent-assisted aneurysm coiling procedures. However, in aneurysms larger than 10 mm in diameter, beam hardening artifacts caused by the endoaneurysmal coil package impair visibility of the stent. Further data are necessary to evaluate the usefulness of ACT in stent-assisted aneurysm coiling.

High Atomic Number Contrast Media Offer Potential for Radiation Dose Reduction in Contrast-Enhanced Computed Tomography - Rößler, Ann-Christin; Hupfer, Martin; Kolditz, Daniel; Jost, Gregor; Pietsch, Hubertus; Kalender, Willi Alfred (Investigative Radiology, 2015)
Spectral optimization of x-ray computed tomography (CT) has led to substantial radiation dose reduction in contrast-enhanced CT studies using standard iodinated contrast media. The purpose of this study was to analyze the potential for further dose reduction using high-atomic-number elements such as hafnium and tungsten. As in previous studies, spectra were determined for which the patient dose necessary to provide a given contrast-to-noise ratio (CNR) is minimized.We used 2 different quasi-anthropomorphic phantoms representing the liver cross-section of a normal adult and an obese adult patient with the lateral widths of 360 and 460 mm and anterior-posterior heights of 200 and 300 mm, respectively. We simulated and measured on 2 different scanners with x-ray spectra from 80 to 140 kV and from 70 to 150 kV, respectively. We determined the contrast for iodine-, hafnium-, and tungsten-based contrast media, the noise, and 3-dimensional dose distributions at all available tube voltages by measurements and by simulations. The dose-weighted CNR was determined as optimization parameter.Simulations and measurements were in good agreement regarding their dependence on energy for all parameters investigated. Hafnium provided the best performance for normal and for obese patient phantoms, indicating a dose reduction potential of 30% for normal and 50% for obese patients at 120 kV compared with iodine; this advantage increased further with higher kV values. Dose-weighted CNR values for tungsten were always slightly below the hafnium results. Iodine proved to be the superior choice at voltage values of 80 kV and below.Hafnium and tungsten both seem to be candidates for contrast-medium-enhanced CT of normal and obese adult patients with strongly reduced radiation dose at unimpaired image quality. Computed tomography examinations of obese patients will decrease in dose for higher kV values.
EVALuna2:10116

Image quality of ultra-low radiation exposure coronary CT angiography with an effective dose <0.1 mSv using high-pitch spiral acquisition and raw data-based iterative reconstruction - Schuhbaeck, Annika; Achenbach, Stephan; Layritz, Christian; Eisentopf, Jasmin; Hecker, Franziska; Pflederer, Tobias; Gauss, Soeren; Rixe, Johannes; Kalender, Willi Alfred; Daniel, Werner; Lell, Michael; Ropers, Dieter (European Radiology, 2013)
Objectives: We evaluated the potential of prospectively ECG-triggered high-pitch spiral acquisition with low tube voltage and current in combination with iterative reconstruction to achieve coronary CT angiography with sufficient image quality at an effective dose below 0.1 mSv. Methods: Contrast-enhanced coronary dual source CT angiography (2 × 128 × 0.6 mm, 80 kV, 50 mAs) in prospectively ECG-triggered high-pitch spiral acquisition mode was performed in 21 consecutive individuals (body weight <100 kg, heart rate ≤60/min). Images were reconstructed with raw data-based filtered back projection (FBP) and iterative reconstruction (IR). Image quality was assessed on a 4-point scale (1 = no artefacts, 4 = unevaluable). Results: Mean effective dose was 0.06 ± 0.01 mSv. Image noise was significantly reduced in IR (128.9 ± 46.6 vs. 158.2 ± 44.7 HU). The mean image quality score was lower for IR (1.9 ± 1.1 vs. 2.2 ± 1.0, P < 0.0001). Of 292 coronary segments, 55 in FBP and 40 in IR (P = 0.12) were graded "unevaluable". In patients with a body weight ≤75 kg, both in FBP and in IR, the rates of fully evaluable segments were significantly higher in comparison to patients >75 kg. Conclusions: Coronary CT angiography with an estimated effective dose <0.1 mSv may provide sufficient image quality in selected patients through the combination of high-pitch spiral acquisition and raw data-based iterative reconstruction. Key Points: • Coronary CT angiography with an estimated effective dose <0.1 mSv is possible. • Combination of high-pitch spiral acquisition with iterative reconstruction achieves sufficient image quality. • Diagnostic accuracy remains to be assessed in future trials. © 2012 European Society of Radiology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dual source CT; High-pitch spiral acquisition; Image quality; Iterative reconstruction; Ultra low-dose coronary CT angiography

Investigation of spectral performance for single-scan contrast-enhanced breast CT using photon-counting technology: A phantom study - Ruth, Veikko; Kolditz, Daniel; Steiding, Christian; Kalender, Willi Alfred (Medical Physics, 2020)
Purpose: Contrast-enhanced imaging of the breast is frequently used in breast MRI and has recently become more common in mammography. The purpose of this study was to make single-scan contrast-enhanced imaging feasible for photon-counting breast CT (pcBCT) and to assess the spectral performance of a pcBCT scanner by evaluating iodine maps and virtual non-contrast (VNC) images. Methods: We optimized the settings of a pcBCT to maximize the signal-to-noise ratio between iodinated contrast agent and breast tissue. Therefore, an electronic energy threshold dividing the x-ray spectrum used into two energy bins was swept from 23.17 keV to 50.65 keV. Validation measurements were performed by placing syringes with contrast agent (2.5 mg/ml to 40 mg/ml) in phantoms with 7.5 cm and 12 cm in diameter. Images were acquired at different tube currents and reconstructed with 300 μm isotropic voxel size. Iodine maps and VNC images were generated using image-based material decomposition. Iodine concentrations and CT values were measured for each syringe and compared to the known concentrations and reference CT values. Results: Maximal signal-to-noise ratios were found at a threshold position of 32.59 keV. Accurate iodine quantification (average root mean square error of 0.56 mg/ml) was possible down to a concentration of 2.5 mg/ml for all tube currents investigated. The enhancement has been sufficiently removed in the VNC images, so they can be interpreted as unenhanced CT images. Only minor changes of CT values compared to a conventional CT scan were observed. Noise was increased by the decomposition by a factor of 2.62 and 4.87 (7.5 cm and 12 cm phantoms) but did not compromise the accuracy of the iodine quantification. Conclusions: Accurate iodine quantification and generation of VNC images can be achieved using contrast-enhanced pcBCT from a single CT scan in the absence of temporal or spatial misalignment. Using iodine maps and VNC images, pcBCT has the potential to reduce dose, shorten examination and reading time, and to increase cancer detection rates.
CRIS-Team Scopus Importer:2020-04-28
Keywords: breast CT; contrast enhanced; iodine quantification; photon-counting; spectral imaging

Körperliches Training und Frakturparameter - Kemmler, Wolfgang; von Stengel, Simon; Mayer, Sabine; Engelke, Klaus; Kalender, Willi Alfred (Bewegungstherapie und Gesundheitssport, 2009)
UnivIS-Import:2015-04-14:Pub.2009.phil.dps.iss.psbg.krperl

Metal Artifact Reduction in X-ray Computed Tomography Using Computer-Aided Design Data of Implants as Prior Information - Ruth, Veikko; Kolditz, Daniel; Steiding, Christian; Kalender, Willi Alfred (Investigative Radiology, 2017)
OBJECTIVES: The performance of metal artifact reduction (MAR) methods in x-ray computed tomography (CT) suffers from incorrect identification of metallic implants in the artifact-affected volumetric images. The aim of this study was to investigate potential improvements of state-of-the-art MAR methods by using prior information on geometry and material of the implant. MATERIALS AND METHODS: The influence of a novel prior knowledge-based segmentation (PS) compared with threshold-based segmentation (TS) on 2 MAR methods (linear interpolation [LI] and normalized-MAR [NORMAR]) was investigated. The segmentation is the initial step of both MAR methods. Prior knowledge-based segmentation uses 3-dimensional registered computer-aided design (CAD) data as prior knowledge to estimate the correct position and orientation of the metallic objects. Threshold-based segmentation uses an adaptive threshold to identify metal. Subsequently, for LI and NORMAR, the selected voxels are projected into the raw data domain to mark metal areas. Attenuation values in these areas are replaced by different interpolation schemes followed by a second reconstruction. Finally, the previously selected metal voxels are replaced by the metal voxels determined by PS or TS in the initial reconstruction. First, we investigated in an elaborate phantom study if the knowledge of the exact implant shape extracted from the CAD data provided by the manufacturer of the implant can improve the MAR result. Second, the leg of a human cadaver was scanned using a clinical CT system before and after the implantation of an artificial knee joint. The results were compared regarding segmentation accuracy, CT number accuracy, and the restoration of distorted structures. RESULTS: The use of PS improved the efficacy of LI and NORMAR compared with TS. Artifacts caused by insufficient segmentation were reduced, and additional information was made available within the projection data. The estimation of the implant shape was more exact and not dependent on a threshold value. Consequently, the visibility of structures was improved when comparing the new approach to the standard method. This was further confirmed by improved CT value accuracy and reduced image noise. CONCLUSIONS: The PS approach based on prior implant information provides image quality which is superior to TS-based MAR, especially when the shape of the metallic implant is complex. The new approach can be useful for improving MAR methods and dose calculations within radiation therapy based on the MAR corrected CT images.
EVALuna2:33262

Optical measurement of dimensional parameters of the breast with subjects in prone position - Rößler, Ann-Christin; Althoff, Felix; Jaeger, Florian; Kalender, Willi Alfred; Wenkel, Evelyn (Journal of Medical Imaging, 2015)
Various applications require information on breast parameters, such as breast length and volume. An optical system was designed and tested for measuring these parameters with subjects in a prone position. The study results were used for optimizing patient positioning and handling for a future breast computed tomography (BCT) system. Measurements were conducted using an optical measurement system. To test the functionality and accuracy of the system, measurements were performed using reference phantoms. Additionally, 20 women and 5 men were examined to calculate breast parameters in alternative positions and breathing states. The results of the optical measurements were compared with magnetic resonance imaging (MRI) measurements. Volume and length of the reference phantoms were determined with errors below 2%. The patient study demonstrated a mean breast volume of 530.7 ml for women during normal breathing. During an exhalation state, breast volume increased significantly by 17.7 ml in comparison with normal breathing. Differences with MRI measurements were found to be 3% for breast length and 9% for breast volume on average. The proposed optical measurement system was found to be suitable for measuring the dimensional parameters of the breast in a prone position and provides a tool for evaluating breast coverage for BCT.
EVALuna2:10117

Performance of Photon-Counting Breast Computed Tomography, Digital Mammography, and Digital Breast Tomosynthesis in Evaluating Breast Specimens - Rößler, Ann-Christin; Kalender, Willi Alfred; Kolditz, Daniel; Steiding, Christian; Ruth, Veikko; Preuss, Caroline; Peter, Sandra Christina; Brehm, Barbara; Hammon, Matthias; Schulz-Wendtland, Rüdiger; Wenkel, Evelyn (Academic Radiology, 2017)
This study compared a novel photon-counting breast computed tomography (pcBCT) system with digital mammography (DM) and digital breast tomosynthesis (DBT) systems. For this reason, surgical specimens were examined with all three techniques and rated by three observers.A total of 30 surgical specimens were investigated with DM, DBT, and pcBCT; the associated images were shown to three experienced radiologists. Findings (22 microcalcifications and 23 mass lesions) were recorded and compared to the results of the pathological examination. Sensitivity and specificity for detection of microcalcifications and lesions were calculated and displayed using receiver operating characteristic curves.Sensitivity for microcalcifications was 82% for DM, 70% for DBT, and 85% for pcBCT. Specificity for microcalcifications was 71% for DM, 75% for DBT, and 83% for pcBCT. Sensitivity for lesions was 45% for DM, 62% for DBT, and 65% for pcBCT. Specificity for lesions was 76% for DM, 62% for DBT, and 76% for pcBCT.pcBCT showed a comparable or superior performance compared to the clinically approved DM and DBT systems. Mass lesion detectability can be increased further by the use of contrast media.
EVALuna2:14619

Screening for breast cancer with Breast-CT in a ProHTA simulation - Ruile, Georg; Djanatliev, Anatoli; Kriza, Christine; Meier, Florian; Leb, Ines; Kalender, Willi Alfred; Kolominsky-Rabas, Peter (Journal of Comparative Effectiveness Research, 2015)
Aims: The potential of dedicated Breast-CT is evaluated by simulating its impact onto the performance of the German breast cancer screening program. Attendance rates, cancer detection and economic implications are quantified. Methods: Based on a prospective health technology assessment approach, we simulated screening in different scenarios. Results: In the simulation, attendance rates increase from 54 to up to 72% due to reduced pain. Breast cancers will be detected earlier while nodal positives and distant recurrences decrease. Assuming no additional cost, cost savings of up to 55 million in one screening period are computed. Conclusion: The simulation indicates that earlier cancer detection, fewer unnecessary biopsies and less pain are potential benefits of Breast-CT resulting in cost savings and higher attendance.
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.screen
Keywords: breast cancer; computed tomography; health economics; health technology assessment; mammography screening; simulation

Securing safe and informative thoracic CT examinations-Progress of radiation dose reduction techniques - Kubo, Takeshi; Ohno, Yoshiharu; Seo, Joon Beom; Yamashiro, Tsuneo; Kalender, Willi Alfred; Lee, Chang Hyun; Lynch, David A.; Kauczor, Hans Ulrich; Hatabu, Hiroto (European Journal of Radiology, 2017)
The increase in the radiation exposure from CT examinations prompted the investigation on the various dose-reduction techniques. Significant dose reduction has been achieved and the level of radiation exposure of thoracic CT is expected to reach the level equivalent to several chest X-ray examinations. With more scanners with advanced dose reduction capability deployed, knowledge on the radiation dose reduction methods has become essential to clinical practice as well as academic research. This article reviews the history of dose reduction techniques, ongoing changes brought by newer technologies and areas of further investigation.
EVALuna2:33263

Technical feasibility proof for high-resolution low-dose photon-counting CT of the breast - Kalender, Willi Alfred; Kolditz, Daniel; Steiding, Christian; Ruth, Veikko; Lück, Ferdinand; Rossler, Ann-Christin; Wenkel, Evelyn (European Radiology, 2017)
X-ray computed tomography (CT) has been proposed and evaluated multiple times as a potentially alternative method for breast imaging. All efforts shown so far have been criticized and partly disapproved because of their limited spatial resolution and higher patient dose when compared to mammography. Our concept for a dedicated breast CT (BCT) scanner therefore aimed at novel apparatus and detector design to provide high spatial resolution of about 100 ?m and average glandular dose (AGD) levels of 5 mGy or below. Photon-counting technology was considered as a solution to reach these goals. The complete concept was previously evaluated and confirmed by simulations and basic experiments on laboratory setups. We here present measurements of dose, technical image quality parameters and surgical specimen results on such a scanner. For comparison purposes, the specimens were also imaged with digital mammography (DM) and breast tomosynthesis (BT) apparatus. Results show that photon-counting BCT (pcBCT) at 5 mGy AGD offers sufficiently high 3D spatial resolution for reliable detectability of calcifications and soft tissue delineation.o Photon-counting detector technology allows for spatial resolution better than 100 ?m. o pcBCT allows for dose levels in the screening mammography range. o pcBCT provides the highest quality imaging of microcalcifications.
EVALuna2:14668

Training, Risikofaktoren und Gesundheitskosten älterer Menschen: Senioren Fitness und Präventionsstudie (SEFIP) - Kemmler, Wolfgang; von Stengel, Simon; Mayer, Sabine; Engelke, Klaus; Kalender, Willi Alfred (Deutsche Zeitschrift für Sportmedizin, 2010)